Modeling of Adhesively Bonded Joints - da Silva, Lucas F. M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
A lot of recent developments have been made about adhesively bonded joints modeling using various methods of analysis. The increasing application of adhesives in industry is partly due to the increased sophistication and reliability of adhesive joints modeling. The book proposed intends to provide the designer with the most advanced stress analyses techniques in adhesive joints to reinforce the use of this promising bonding technique.
Analytical Modeling -- Simple Lap Joint Geometry -- Analysis of Cracked Lap Shear (CLS) Joints -- Analytical Models with Stress Functions -- Numerical Modeling -- Complex Constitutive Adhesive Models -- Complex Joint Geometry -- Progressive Damage Modelling -- Modelling Fatigue in Adhesively Bonded Joints -- Environmental Degradation -- Non-Linear Thermal Stresses in Adhesive Joints -- Impact -- Stress Analysis of Bonded Joints by Boundary Element Method.
Keywords: Mechanics; Mechanics, Applied; Industrial engineering; Production engineering; Materials science; Solid Mechanics; Solid Mechanics; Industrial and Production Engineering; Materials Science, general